EFEKTIVITAS SISTEM INFORMASI KEPEGAWAIAN (SIMPEG) DALAM MANAJEMEN SUMBER DAYA MANUSIA DI BKPSDM KOTA SERANG - Rohaimudin, Iim; Aulia, Sigit (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study explores the effectiveness of the Personnel Information System (SIMPEG) in supporting human resource management at the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Serang City. The study aims to evaluate the extent to which SIMPEG enhances efficiency, accuracy, and transparency in managing civil servant data. A qualitative descriptive approach was used, involving data collection through observation, interviews, and documentation. The findings reveal that SIMPEG supports key functions such as personnel data management, online leave administration, performance evaluation, and career development. However, challenges such as limited user skills, infrastructure limitations, and lack of system integration still exist. To address these, the study recommends conducting regular user training, improving network infrastructure, and integrating SIMPEG with other administrative systems. These efforts are expected to maximize SIMPEG's potential in promoting good governance in public personnel administration